The Effect of Service Quality on Customer Satisfaction at Masagung Workshop During a Pandemic Covid 19: Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Bengkel Masagung Dalam Masa Pandemi Covid 19 - Utomo, Priyo; Krisnanti, Maria; Zaman, Komarun; Hendriawan, Ayi; Manan, Abdul (Procedia of Social Sciences and Humanities, 2022)
In the management of services during the COVID-19 pandemic, there are various kinds of assessments from service users about the Masagung Auto Body Repair workshop. The problem of service that does not satisfy customers is a separate lesson for Masagung's workshop in making considerations to evaluate the company's performance, in order to avoid a decrease in consumer interest in the future. This study aims to determine how far the level of service quality that has been provided by Masagung to customers when viewed from the dimensions of service quality by using a quantitative approach to the associative method. The results of this study are based on partial tests and simple linear regression, in data processing using a Likert scale and also using a scatterplot. The data studied are the results of the answers of respondents who make vehicle repairs at Masagung Workshop. The sample used is the consumers who come to visit Masagung Workshop to do car repairs. The conclusion in this study is that service quality has a significant effect on customer satisfaction, this can be seen in the t test where t count is 3.452 > t table value is 1.987 with a significant 0.001 and a coefficient value of 0.131. This shows that the quality of service provided by the Masagung workshop is a factor that greatly influences the satisfaction of customers who come to the Masagung workshop.